Stretching and transforming research practise for HIV and AIDS curriculum integration: An auto-ethnography - van Laren, L. (South African Journal of Higher Education, 2018)
This paper explores stretching and transforming my research expertise in HIV and AIDS curriculum integration. As a mathematics teacher educator in higher education, I actively pursue ways of enhancing and improving production of new knowledge through alternative research strategies. This study focuses on how my involvement in a Higher Education HIV/AIDS Programme (HEAIDS) HIV and AIDS Education Community of Practice in Higher Education Institutions (CoP) contributed to changing my higher education curriculum research to accommodate the HIV and AIDS context in South Africa. My research question is: How has my participation in the HEAIDS CoP contributed to changing my research practice in HIV and AIDS curriculum integration? I explore HEAIDS CoP contributions to my professional research capacity development using auto-ethnographical methods, using a crocheted artefact as a metaphor to understand my research practice development. Key findings point to the complex, folded, twisted, interwoven nature of reflexivity in my professional learning.